Remote Sensing Image Recovery and Enhancement by Joint Blind Denoising and Dehazing - Yan Cao; Jianchong Wei; Sifan Chen; Baihe Chen; Zhensheng Wang; Zhaohui Liu; Chengbin Chen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
Due to the hazy weather and the long-distance imaging path, the captured remote sensing image (RSI) may suffer from detail loss and noise pollution. However, simply applying dehazing operation on a noisy hazy image may result in noise amplification. Therefore, in this article, we propose joint blind denoising and dehazing for RSI recovery and enhancement to address this problem. First, we propose an efficient and effective noise level estimation method based on quad-tree subdivision and integrate it into fast and flexible denoising convolutional neural network for blind denoising. Second, a multiscale guided filter decomposes the denoised hazy image into base and detailed layers, separating the initial details. Then, the dehazing procedure using the corrected boundary constraint is implemented in the base layer, while a nonlinear sigmoid mapping function enhances the detailed layers. The last step is to fuse the enhanced detailed layers and the dehazed base layer to get the final result. Using both synthetic remote sensing hazy image (RSHI) datasets and real-world RSHI, we perform comprehensive experiments to evaluate the proposed method. Results show that our method is superior to well-known methods in both dehazing and joint denoising and dehazing tasks.